2008
DOI: 10.1016/j.cellbi.2007.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ROS burst as an early sign in sarsasapogenin‐induced apoptosis in HepG2 cells

Abstract: Sarsasapogenin is a steroidal sapogenin with antitumor properties. To explain the mechanism of its apoptotic effect, mitochondrial activity was assessed via a 3,(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Flow cytometry (FCM) was used to estimate the changes in mitochondrial membrane potential (MMP), reactive oxygen species (ROS) generation, and cellular-reduced glutathione (GSH) level. Laser scanning confocal microscope (LSCM) recorded instantaneous ROS burst after application of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…These results indicate that DHMEQ induced ER stress in a Ca 2ϩ -independent mechanism. Recent reports point to mitochondria as a critical apoptotic checkpoint at which converge ROS generation and ER stress response (Ni et al, 2008;Pinton et al, 2008). Our results point to mitochondrial generation of ROS induced by DH-MEQ.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…These results indicate that DHMEQ induced ER stress in a Ca 2ϩ -independent mechanism. Recent reports point to mitochondria as a critical apoptotic checkpoint at which converge ROS generation and ER stress response (Ni et al, 2008;Pinton et al, 2008). Our results point to mitochondrial generation of ROS induced by DH-MEQ.…”
Section: Discussionsupporting
confidence: 64%
“…Consequently, in this study, we observed the activation of caspases-3/7 and -9, and the cleavage of PARP, a well known caspase-3 target, which were triggered by DHMEQ in a ROSdependent manner. Therefore, our data link ROS generation with mitochondrial apoptotic pathway and caspase activation as reported by others (Meeran et al, 2008;Ni et al, 2008). Moreover, the levels of survivin, an antiapoptotic protein member of the inhibitor of apoptosis (IAP) family, were reduced by DHMEQ treatment, and this was dependent on ROS production, as reported in other cancer cells (Zhang et al, 2008).…”
Section: Discussionsupporting
confidence: 61%
“…In fact, Chen et al report that intracellular ROS, detected by 2',7'-dichlorofluorescin diacetate (DCFDA) and dihydroethidium (DHE), gradually increased in multiple myeloma IM-7 and RPMI8226 cells after γ irradiation [13]. As a source of late intracellular ROS, the respiratory chain in mitochondria has been proposed in tumor cells exposed to genotoxic stimuli [14,15]. However, there is no direct evidence for a radiation-induced late increase of intracellular ROS derived from mitochondria because the sensitivity and specificity of fluorescence probes and spin-trapping reagents to detect ROS are insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Within several hours after irradiation, secondary ROS production occurs intracellularly, and it induces apoptosis (22,23). Mitochondria are well known as a major source of intracellular ROS and produce ROS during intracellular ATP synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria are well known as a major source of intracellular ROS and produce ROS during intracellular ATP synthesis. Therefore, the source of secondary ROS as a result of irradiation is thought to be the mitochondria (22)(23)(24). The generation of ROS from mitochondria and the loss of the mitochondrial membrane potential play an important role in inducing cell death (23,25,26).…”
Section: Introductionmentioning
confidence: 99%